A Large Entropic Term Due to Water Rearrangement is Concomitant with the Photoproduction of Anionic Free-Base Porphyrin Triplet States in Aqueous Solutions - Andrés, Gabriel O. (2007)
The enthalpy change, DTH, and volume change, DTV, associated with triplet state formation upon excitation of free-base meso-tetra-(4-sulfonatophenyl)porphyrin, TSPP4-, its Zn derivative, ZnTSPP4-, and meso-tetra-(4-carboxyphenyl)porphyrin, TCPP4-, were obtained in aqueous solutions by the application of laser-induced optoacoustics spectroscopy (LIOAS) in the presence of phosphate salts of various monovalent cations (Li+, Na+, K+, NH4 +, and Cs+).A linear correlation was found between DTH and DTV at different phosphate concentrations for the free-base porphyrins. The intercepts (132±8 kJ mol-1 for TSPP4- and 164±23 kJ mol-1 for TCPP4- of these plots correspond to the respective value of the triplet energy content obtained from phosphorescence at 77 K (140 and 149 kJ mol-1). This suggests thatDTG for the triplet state formation is independent of the medium and an enthalpy-entropy compensation is responsible for the much smaller and salt-dependent DTH values obtained at room temperature. The Gibbs energy for triplet state formation of the free-base porphyrins at room temperature is thus mainly determined by the entropic term due to solvent rearrangement. The DTH values for 3ZnTSPP4- at different buffer concentrations and differentcations are all between 130 and 150 kJ mol-1, close to the triplet energy obtained from phosphorescence (ET = 155 kJ mol-1). The solvent structure and the nature of the counterion have a negligible influence on the 3ZnTSPP4- formation due to the blockage of the electron pairs on the central N atoms. Thus, the small DTV value should be due to intrinsic bond changes upon 3ZnTSPP4- formation and no correlation between DTH and DTV should be expected in this case. The enthalpy change determines the Gibbs energy for 3ZnTSPP4- formation at room temperature.